Students' Perceptions about The Use of Youtube in Improving Listening Comprehension Skills on Online Learning - Auliah, Wahyuli; Abduh, Amirullah; Korompot, Chairil Anwar (State University of Makassar, 2022)
This research was conducted to find out Students perceptions about the use of YouTube in learning English in online learning. The researcher used descriptive qualitative method to achieve the research objectives. The data collected in this study were in the form of interviews. The participants of this study were Students of SMK Negeri 4 Gowa as informants. The interview sample was 10 students, using purposive sampling technique. Based on the results of the study, YouTube could help Students in learning English in improving listening comprehension However, Students also faced some challenges in using YouTube as a media in learning. In listening comprehension, Students coud understand the material and practice their ability in vocabulary and listening skills, they argued that YouTube is a media that helps them to learn English. In action, students experienced changes in learning behavior in understanding English materials. Then, Students felt that their vocabulary increased and the pronunciation of words became better by using YouTube. This shows that Students consider that learning English by using YouTube media can improve their understanding of learning materials.Keywords : Students perceptions, YouTube, listening comprehension, online learning.